Pengaruh Pergantian Auditor, Fee Auditor, Dan Kepemilikan Asing Terhadap Penerimaan Opini Audit Going Concern Dengan Spesialisasi Auditor Sebagai Variabel Moderasi - Oktavia Wardani (Perspektif Akuntansi, 2019)
The purpose of this research is to examine and analyze the effect of auditor switching, auditor fee and foreign ownership on the acceptance of going concern opinion with auditor specialization as a moderating variable. The population used in this study were companies that are listed on the Indonesia Stock Exchange (IDX) between 2014 and 2017. The samples in this study were selected by purposive sampling method with 40 companies that met the criteria. The testing are done using logistic regression analysis. The results show auditor switching and auditor fees are not affect the acceptance of going-concern audit opinion. While the foreign ownership variable has a negative effect on the acceptance of going-concern audit opinion. In addition, the results of this study also state that auditor specialization does not weaken the negative influence of auditor turnover on the acceptance of going concern audit opinion. However, it strengthens the positive effect of auditor fees on the acceptance of going-concern audit opinion and weakens the negative influence of foreign ownership on the acceptance of going-concern audit opinion.